2019
DOI: 10.1021/acs.macromol.8b02714
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Orientational and Network Dynamics of Polydisperse Nanofibers on the Nanoscale

Abstract: Polydisperse fibre networks are the basis of many natural and man-made architectures, ranging from high-performance bio-based materials to components of living cells and tissues. The formation and persistence of such networks are given by fibre properties such as length and stiffness as well as the number density and fibre-fibre interactions. Studies of fibre network behavior, such as connectivity or rigidity thresholds, typically assume fixed fibre length and isotropic fibre orientation distributions, specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…This showed that the rotary diffusion process includes multiple time scales. Subsequent work showed how these different time scales can be attributed to the polydispersity of the dispersion, [86,87] where the fastest time-scales for dealignment relate to short, nonentangled nanofibrils, while the longest timescales rather relate to longer nanofibrils, which are at least partially entangled in a loose network. Using this POM flow-stop technique, it is thus possible to probe collective dynamics, which can be used to estimate sizes/ lengths and interactions of the nanofibrils.…”
Section: Measuring Differences In Refractive Indicesmentioning
confidence: 99%
“…This showed that the rotary diffusion process includes multiple time scales. Subsequent work showed how these different time scales can be attributed to the polydispersity of the dispersion, [86,87] where the fastest time-scales for dealignment relate to short, nonentangled nanofibrils, while the longest timescales rather relate to longer nanofibrils, which are at least partially entangled in a loose network. Using this POM flow-stop technique, it is thus possible to probe collective dynamics, which can be used to estimate sizes/ lengths and interactions of the nanofibrils.…”
Section: Measuring Differences In Refractive Indicesmentioning
confidence: 99%
“…As shown in Figure 2, colloids displaying high hydrophilicity and water affinity can produce stable aqueous suspensions. Typically, nanoparticles move randomly in water by Brownian mechanisms and under electrostatic and other colloidal interactions (Brouzet et al 2019). It has been shown that the source of precursor material, nanoparticle aspect ratio, medium viscosity, as well as solid content have strong impact on the ensuing fibre properties (Lundahl et al 2016a(Lundahl et al , 2017.…”
Section: Wet Spinningmentioning
confidence: 99%
“…Furthermore, the variety of different pre-treatments and mechanical delamination processes results in a plethora of different CNF qualities, varying in both chemical and mechanical properties (Klemm et al 2011). Elucidating how the CNF properties, such as size, stiffness, residual fiber fragment proportion and chemical composition influence the static and dynamic bulk properties of the corresponding suspensions, and the time dependency thereof, is an active research field with many unknowns (Brouzet et al 2018(Brouzet et al , 2019Rosen et al 2020). Alongside the studies of connecting the CNF properties with the suspension properties, the suspensions are used and formed into 1D filaments, 2D films and 3D objects.…”
Section: Introductionmentioning
confidence: 99%